Proceedings of the 21st ACM Symposium on Virtual Reality Software and Technology 2015
DOI: 10.1145/2821592.2821609
|View full text |Cite
|
Sign up to set email alerts
|

Procedural techniques for simulating the growth of plant leaves and adapting venation patterns

Abstract: This paper presents biologically-motivated a procedural method for the simulation of leaf contour growth and venation development. We use a mathematical model for simulating the growth of a plant leaf. Leaf tissue is regarded as a viscous, incompressible fluid whose 2D expansion is determined by a spatially varying growth rate. Visually realistic development is described by a growth function RERG that reacts to hormone (auxin) sources embedded in the leaf blade. The shape of the leaf is determined by a set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…One such study includes a modeling method that applies the CGA Shape grammar to the growth of digital plants based on the convolution sums of divisor functions [13]. Other examples include a study using hierarchical topology-preserving, blending, and morphing techniques for tree modeling [14,15], another study involving a method for modeling trees using local convolution surface approximation, and yet another study based on simulating the growth of plant leaves that are composed of Voronoi diagrams [17]. However, these studies have shown limitations in the context of effectively generating various digital plants, since they lack in the aspect of intuitiveness from the user's perspective.…”
Section: Previous Workmentioning
confidence: 99%
“…One such study includes a modeling method that applies the CGA Shape grammar to the growth of digital plants based on the convolution sums of divisor functions [13]. Other examples include a study using hierarchical topology-preserving, blending, and morphing techniques for tree modeling [14,15], another study involving a method for modeling trees using local convolution surface approximation, and yet another study based on simulating the growth of plant leaves that are composed of Voronoi diagrams [17]. However, these studies have shown limitations in the context of effectively generating various digital plants, since they lack in the aspect of intuitiveness from the user's perspective.…”
Section: Previous Workmentioning
confidence: 99%
“…Later, Pirk et al automatically infer the developmental parameters from one single static tree and then interpolates them to generate the tree growth animations. Environmental factors, including obstacles, lighting, winds, and competition with other trees have been studied to date to realistically animate interactions between trees and the environment. However, none of them is capable of generating fluid morphing between topologically varying trees.…”
Section: Related Workmentioning
confidence: 99%
“…The transformation of one‐to‐many matched chains is achieved by split or merge operations. The in‐between trunks are interpolated and then reconstructed using the method of Alsweis et al…”
Section: Morphingmentioning
confidence: 99%